Internationalization field lab of Ps: an in-depth analysis of Sweden - Cardoso, Diogo Soares (2022)
Internationalization is a strategic challenge for small companies. This paper aims to provide an analytic procedure for the Portuguese luxury real estate agency of PS by defining the target market for expansion, an appropriate market entry mode, and an applicable marketing plan along with a financial forecast. Firstly, literature regarding the differences among export and foreign direct investment entry modes were analyzed. Secondly, it was performed an in-depth analysis of Sweden, which revealed to be an attractive country apart from the competitive landscape and the market and company sales potential, which, among others, are negatively affected by the Scandinavian culture.